Study on Certain Subclass of Analytic Functions Involving Mittag-Leffler Function - Nazek Alessa (Hindawi Limited, 2021)
We propose and explore a new subclass of regular functions described by a new derivative operator in this paper. Some coefficient estimations, growth and distortion aspects, extreme points, star-like radii, convexity, Fekete-Szego inequality, and partial sums are derived.